Passive restoration of vegetation and biological soil crusts following 80 years of exclusion from grazing across the Great Basin. (3rd October 2019) - Condon, Lea A.; Pietrasiak, Nicole; Rosentreter, Roger; Pyke, David A.
Abstract : Restoration targets for biological soil crusts are largely unknown. We surveyed seven 80‐year‐old grazing exclosures across northern Nevada for biocrusts to quantify reference conditions at relatively undisturbed sites. Exclosures were associated with the following plant communities: Wyoming big sagebrush, black sagebrush, and areas co‐dominated by winterfat and Wyoming big sagebrush. Cover of biocrusts and shrubs were generally higher than other plant groups at these sites, regardless of being inside or outside of the exclosures, suggesting these groups make up most of the native flora across the region. Important in forming soil structure, cyanobacteria of the order Oscillatoriales were less abundant and diverse in black sagebrush communities. Grazing had a negative effect on the abundance of Oscillatoriales but not the number of algal taxa, including cyanobacteria. Abundance of light algal crusts were not influenced by plant community or grazing. Dark algal crusts were generally less abundant on grazed sites. Influences of plant community and grazing were most apparent when accounting for reproductive rates of lichens and mosses based on establishment mechanisms. Abundance of shrubs, perennial grasses, Oscillatoriales, fast reproducing biocrusts and the number of algal and cyanobacterial taxa, varied by plant community, suggesting that restoration should be plant community specific. We demonstrate the affinity of rapidly reproducing biocrusts for winterfat‐Wyoming big sagebrush co‐dominated plant communities, regardless of grazing pressure. Across sites, the effects of grazing were most evident on the abundance of Oscillatoriales and slowly reproducing biocrusts following 80 years of cessation from grazing.